Antibiotics-free compounds for managing carbapenem-resistant bacteria; a narrative review - Shariati, Aref; Kashi, Milad; Chegini, Zahra; Hosseini, Seyed Mostafa (Frontiers in Pharmacology, 2024)
Carbapenem-resistant (CR) Gram-negative bacteria have become a significant public health problem in the last decade. In recent years, the prevalence of CR bacteria has increased. The resistance to carbapenems could result from different mechanisms such as loss of porin, penicillin-binding protein alteration, carbapenemase, efflux pump, and biofilm community. Additionally, genetic variations like insertion, deletion, mutation, and post-transcriptional modification of corresponding coding genes could decrease the susceptibility of bacteria to carbapenems. In this regard, scientists are looking for new approaches to inhibit CR bacteria. Using bacteriophages, natural products, nanoparticles, disulfiram, N-acetylcysteine, and antimicrobial peptides showed promising inhibitory effects against CR bacteria. Additionally, the mentioned compounds could destroy the biofilm community of CR bacteria. Using them in combination with conventional antibiotics increases the efficacy of antibiotics, decreases their dosage and toxicity, and resensitizes CR bacteria to antibiotics. Therefore, in the present review article, we have discussed different aspects of non-antibiotic approaches for managing and inhibiting the CR bacteria and various methods and procedures used as an alternative for carbapenems against these bacteria.